ROLE OF INNOVATION ACTIVITY IN THE ECONOMY PROBLEMS OF ENSURING INNOVATIVE ACTIVITY IN THE ECONOMY (World Economics and Finance Bulletin, 2023)
This article analyzes the theoretical aspects of the country's economy to achieve innovative activity. In the context of globalization, it is necessary to ensure the innovative development of the economy by attracting more investment. Therefore, innovative economic growth can be achieved by further improving the country's investment climate, which is one of the most important and pressing issues of the national economy. It also shows the problems that arise in the process of ensuring innovative activity and directions for their solution
Keywords: innovation activity; globalization processes; national economy